A participação das meninas nas aulas de Educação Física: dilemas de um professor no ensino do futsal - Malvar, Antonio Jorge Martins (Universidade Federal de São Carlos, 2020)
School Physical Education has always faced problems related to the participation of girls in their classes, a situation that, despite the female achievements, continues until the present day. The resistance of girls to participate in practical activities is notorious, especially when this participation takes place in mixed classes and / or requires certain skills not previously explored. This is a qualitative research, type ethnographic study, which has its problem situation materialized in the context of the limited participation of girls less competent sports in the Collective Sports Games (JEC) in Physical Education classes. The objective was to analyze girls' participation in futsal practice in school physical education classes in a 6th grade Elementary Municipal Public School located in the urban area of Feira de Santana - BA. In a futsal teaching unit were used as data collection instruments the class diaries, with records happening immediately after classes, and as a pedagogical strategy the conversation wheels with students, that have been recorded in audio and later transcribed for class diaries. After collecting and reading the analysis corpus, the data were analyzed and categorized through inductive analysis, resulting in the categories "Achievements and overcoming experienced by girls", “Difficulties and challenges faced by girls” and “The teacher's view of the teaching processes of futsal”. From these analyzes it can be inferred that both TGfU and Sport Education have the potential to assist Physical Education teachers in teaching sports at school. It was identified that a group of girls who engaged and participated in classes more effectively presented indicators of evolution from the technical-tactical point of view in futsal. In contrast, it was showed that there was a lack of didactic treatment of attitudinal knowledge who presented themselves as the biggest obstacle to the authentic participation of the majority of girls in classes, insofar as we identified that structural sexism operated through symbolic violence, oppressing and removing these students from classes. It should be noted that this sexism was not exercised without resistance movements on the part of the students, who sometimes expressed their awareness of the mechanisms of oppression and empowered themselves in the process. Despite all the difficulties faced, the speech of one of the girls at the end of the intervention, indicating that boys and girls had to learn to live together, reveals that attitudinal knowledge was being developed throughout the process coeducative, contributing to the rescue of values such as respect for differences, autonomy, interaction and collaboration.
Girls' participation in Physical Education classes: dilemmas of a teacher in futsal teaching
Keywords: Educação Física escolar; Ensino fundamental; Futsal; Meninas; School Physical Education; Elementary school; Futsal; Girls; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM